Effect of ambient temperature on spread of COVID-19: A Systematic Review - Ahad Heyari; Saeed Fallah-aliabadi; Peymaneh Habibi (Shahid Sadoughi University of Medical Sciences, 2021)
Abstract Introduction: So far, the so many people has been infected by novel coronavirus (SARS-CoV-2) in the worldwide and almost all the countries have reported infected and death cases. Some studies have shown that coronaviruses are sensitive to air temperature and in warm temperature the rate of spread decreases. This study aimed to review the literature whether or not the temperature can affect the spread rate of COVID-19.   Methods: In this study, three main scientific electronic databases, including Scopus, PubMed, Web of Science and also Google Scholar were searched on April 14, 2020 to find relevant studies on COVID-19 and its spread in different ambient temperature. Results: Totally 588 articles were found for screening and 27 articles were selected for data extraction. The result of some of these studies showed that weather variations can affect transmission of coronavirus. Low temperature and low humidity may be essential factors for survival of coronaviruses. A temperature of 4°C is ideal for the life of this virus and it may be sensitive to 70°C temperature. The increase in temperature of stainless steel, wood, fabrics, and metal can eliminate and remove coronaviruses according to the findings of some of these reviewed articles. Conclusion: This review study failed to precisely report the effect of temperature or humidity to stop the virus from spreading and transmitting. It is required to conduct more studies in this regard to introduce the exact pattern of transmission by examining the conditions of virus transmission in different climatic conditions.